OP0105 Accumulation of CD34+ hematopoietic stem cells in the initial inflammatory human fracture hematoma is driven by rantes and eotaxin. (23rd January 2014) - Hoff, P.; Gaber, T.; Hahne, M.; Strehl, C.; Fangradt, M.; Schmidt-Bleek, K.; Burmester, G.R.; Schmidmaier, G.; Duda, G.N.; Perka, C.; Buttgereit, F.
Abstract : Background: We have previously shown the early phase of human fracture healing to be characterized by hypoxia which promotes inflammation and chemoattraction. Hypoxia is also known to promote proliferation, survival and migration of different stem/progenitor cells like mesenchymal stem cells, endothelial progenitor cells or hematopoietic stem cells (HSC). However, the clinical relevance of hypoxia and inflammation in the early phase of fracture healing for HSC remains unclear. Objectives: To investigate immunological events in fracture healing, we quantified (i) CD34+ hematopoietic stem cells and (ii) inflammatory chemokines present in the early (<72h) human fracture hematoma (FH) at the fracture gap. To investigate the chronologic development, we also analyzed hematomas which resulted from the transection of the femur in patients receiving a total hip arthroplasty (THA). The THA-hematomas (THA-H) were defined as a model for fracture hematomas at time point 0h. Methods: The proportion of HSC in the fracture hematoma from healthy patients (n=42) and patients receiving a THA (n=20) was analyzed by flow cytometry. Secreted factors were quantified by multiplex suspension array. Results: A fracture destroys bone architecture and vascular network leading to bioenergetically restricted conditions such as hypoxia within the fracture hematoma. Although the cells present have to face those conditions, we were able to find a higher proportion of CD34+ hematopoietic stem cells in the FH as compared to THA-H (7.6±1.5 vs. 3.8±0.5% of mononuclear cells) indicating proliferation and/or immigration of HSC in the FH. As CD34+ hematopoietic stem cells express CCR3, we investigated the concentrations of its ligands RANTES and Eotaxin. Indeed, both chemokines were present at significantly higher concentrations in the FH as compared to THA-H (RANTES: 16867±1632 vs. 9830±1397 pg/ml, p<0.01; Eotaxin: 327±76 vs. 125±15 pg/ml, p<0.001). We also identified the macrophage migration inhibitory factor (MIF) to be significantly increased in the FH (179431±28538 vs. 21751±2973 pg/ml, p<0.001). Conclusions: Hypoxia and other bioenergetically adverse conditions in a FH contribute to the induction of inflammation, including the secretion of RANTES, Eotaxin and MIF. We suppose the high concentrations of RANTES and Eotaxin to facilitate the immigration of CD34+ HSC. The initial hypoxic conditions also mediate the secretion of the proinflammatory MIF which has been already shown to be important for successful fracture healing. Thus, the inflammatory microenvironment in the FH is among the crucial factors determining fracture healing. Disclosure of Interest: None Declared